Rootstocks for ’Bahia’ sweet orange - Soares Filho, Walter dos Santos; Cunha Sobrinho, Almir Pinto da; Passos, Orlando Sampaio (Pesquisa Agropecuaria Brasileira, 2014)
Considering the economic importance of the ’Bahia’ sweet orange as fresh fruit and the lack of information about its behaviour when grafted on different rootstocks, a trial involving this cultivar and nine rootstocks was set, at the "Centro Nacional de Pesquisa de Mandioca e Fruticultura - CNPMF" - in Cruz das Almas, Bahia. A randomized block design, with five replications and three plants per plot at 7 m x 7 m spacing, in a "tabuleiro" type of soil was used. ’Hamlin’ sweet orange and ’Cleópatra’ mandarin gave the best results on vigor, while ’Minneola’ tangelo was the worst one. The most productive trees were those grafted on ’Dancy’ mandarin and ’Palmeiras’ sweet orange, while the least productive were those grafted on ’Minneola’ and ’Sampson’ tangelos and ’Swatow’ mandarin. All rootstocks showed similar behaviour regarding to the fruit quality. The ‘Dancy’ mandarin and the ’Palmeiras’ sweet orange may be indicated as good rootstocks for ’Bahia’ sweet orange under the trial conditions. On the other hand, the ’Flórida’ rough lemon did not show good results, as expected, and thus it is not recommended as a rootstock for this cultivar.